KOMPOSISI BIJI LABU KUNING DALAM SNACK BAR DITINJAU DARI SIFAT FISIK, ORGANOLEPTIK DAN AKTIVITAS ANTIOKSIDAN (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Yellow pumpkin seeds are known to have high antioxidants, but their use as food is still limited. A high level of antioxidants in yellow pumpkin seeds can be used as main ingredient in making snack bar products. In this research, we try to find out the variety of yellow pumpkin seeds composition to making soy bean flour snack bars in terms of physical properties, organoleptic properties and antioxidant activity. This is an experimental research. There were 4 treatments with different ratio of soybean flour and yellow pumpkin seed. Research was conducted in january-february 2022 at Department of Nutrition Politeknik Kesehatan Kementerian Kesehatan Yogyakarta. Physical properties test data were analyzed descriptively, organoleptic properties tests were analyzed using the Kruskal Wallis test and antioxidant activity was analyzed using the One Way Anova test. We offer variation of composition of yellow pumpkin seed in making snack bars and there is an influence of composition variety in mixing yellow pumpkin seeds on the physical properties, organoleptic properties, and antioxidant activity of snack bars.